Healthy Lifestyle Education to Teenagers in The Adaptation Era of New Normal at SMK Negeri 7 Makassar - Kadek Ayu Erika; Nur Fadilah; Sri Ramadany (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
One of the problems for teenagers in the post-pandemic adaptation era is an unhealthy lifestyle. The lifestyle of SMK 7 Makassar students is mostly classified as sedentary life is playing gadgets and sitting relaxed. The importance of healthy lifestyle educational activities and nutritional status screening in teenagers can identify and reduce the risk of disease in children in the future. The purpose of this program is to educate and increase teenagers knowledge about the importance of a healthy lifestyle, assess the nutritional status of teenagers and find out the description of teenagers blood pressure in the adaptation era of new normal at SMK Negeri 7 Makassar. Based on the results of community service activities on 149 teenagers, the average value obtained includes age is 16 years, body weight is 51 kg, height is 155 cm, systolic blood pressure is 110.88 mmHg and diastolic is 71.84 mmHg, good nutritional status is 70.5% and normal blood pressure as much as 81.2%. There was a significant difference in the level of knowledge of teenagers based on the pre-post test after education, namely p=0.001. This shows the importance of education given to teenagers to increase understanding of a healthy lifestyle as a preventive action. The important role of health workers in the Puskesmas work area to identify and intervene the effects of unhealthy lifestyles as well as the support of the school and parents to prevent short and long term health impacts that occur in teenagers.